2020
DOI: 10.1111/ppc.12612
|View full text |Cite
|
Sign up to set email alerts
|

Three spirals: Breastfeeding problems, growth spurts, and postpartum depression

Abstract: The inadequacy experienced in maintaining breastfeeding was tried to be understood within the framework of Meleis' theory, and its relationship with growth spurts and postpartum depression was attempted to be revealed. Design and Methods:The study was planned in a case-control type web-based descriptive research design. Mothers (n = 572), who thought that they experienced breastfeeding problems, constituted the case group of the study, and mothers (n = 524), who thought that they did not experience breastfeedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…During the postpartum period, mothers who had low breastfeeding self-efficacy as well as breastfeeding problems or difficulties, such as pain, discomfort, and concern, were more likely to develop depressive symptoms [ 8 ]. Nevertheless, it has been suggested that mothers will adapt and develop a coping mechanism that will result in fewer breastfeeding problems [ 25 ]. Breastfeeding self-efficacy was found to be inversely correlated with postpartum depression (p < 0.001), although it was not found to be a significant predictor of postpartum depression in the final regression model of this study.…”
Section: Discussionmentioning
confidence: 99%
“…During the postpartum period, mothers who had low breastfeeding self-efficacy as well as breastfeeding problems or difficulties, such as pain, discomfort, and concern, were more likely to develop depressive symptoms [ 8 ]. Nevertheless, it has been suggested that mothers will adapt and develop a coping mechanism that will result in fewer breastfeeding problems [ 25 ]. Breastfeeding self-efficacy was found to be inversely correlated with postpartum depression (p < 0.001), although it was not found to be a significant predictor of postpartum depression in the final regression model of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another topic to highlight is the "preservation of milk" 34 because it is closely related to the duration of maternity leave and the return to work of the mother, agreeing with different authors that the completion of maternal leave and reinsertion of the mother into paid work is an important issue related to stopping BF [35][36][37] . A "breastfeeding crisis" is deeply related to the maternal sensation of lack of milk, which is one of the most prominent causes for stopping BF 38 , and there are still gaps in how to offer effective support in these situations 39 . Finally, the lack of knowledge, skills and attitudes of mothers regarding BF, i.e., the loss of the culture of BF, is another critical point for stopping BF 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, we evidenced that PPD is associated with the perception of the baby as being both less alert and more irritable during lactation. The relationship between breastfeeding problems and depression had been previously reported, especially in the first postpartum days [ 51 , 52 ]. However, the inclusion of maternal perceptions on the baby’s attitude towards lactation is new to the literature [ 53 ].…”
Section: Discussionmentioning
confidence: 99%